Opioid Crisis - Simrat Kaur Sarai; Steven Lippmann (Annals of Psychiatry and Treatment - Peertechz Publications, 2017)
Deaths from opioid overdose in the United States doubled between 2000-2014. An increase in prescription opioid drug-induced fatalities parallels a rise in the frequency of these medications being prescribed. Although the number of legal narcotics sold in this country has nearly quadrupled, there is no change reported in the degree of pain Americans experience. Deaths are most common among those opioid users who are drug dependent, even though overdoses occur in medical and non-medical narcotic users who are not addicted. Public health efforts have focused on providing patients with chronic pain appropriate access to opioid pain relievers, while reducing non-medical usage. However, that alone has been insufficient to curb opioid overdoses. There remains a high opioid-related morbidity and mortality among people with pain, even for those receiving these analgesics for legitimate clinical reasons. Research results demonstrating the safety and efficacy of narcotics for chronic, non-cancer pain are not evident. Surveys of patients prescribed opioids over the long-term indicate that most of them continued to experience significant distress; yet, some of them, also experience greater comfort and were without abuse of medication.  Physicians should avoid unnecessary opioid prescribing for some people with chronic conditions, although it is difficult to predict which patients might be vulnerable to addiction versus who might benefit from these pharmaceuticals. Because of such uncertainty, it is helpful when doctors screen personal and family  histories for substance abuse and provide careful, regular monitoring. Strategies for reducing abuse of prescription analgesic drugs focus on physician prescribing regulations that are thus far not consistently effective.